Nivolumab plus ipilimumab in non-small-cell lung cancer - O'Byrne, Ken (My University, 2019)
Nivolumab and ipilimumab, two therapeutic immune checkpoint inhibitor antibodies that block PD-1and CTLA-4, respectively, have indications in cancer as single agents and in combination. In this Review, we examine the potential role of dual immune checkpoint inhibition with nivolumab plus ipilimumab in the management of patients with previously untreated advanced non-small-cell lung cancer, based on results from the Phase III CheckMate 227 study. Immunotherapies with indications in the first-line treatment of non-small-cell lung cancer include pembrolizumab alone and combined with chemotherapy, andatezolizumab combined with bevacizumab and chemotherapy. CheckMate 227 is the first Phase III study evaluating first-line chemotherapy-sparing combination immunotherapy and including tumor mutational burden as a biomarker for patient selection.
Keywords: Atezolizumab; CTLA-4; Nivolumab; Non-small-cell lung cancer; Pem-brolizumab; PD-1; PD-L1; Tumor mutational burden; Immunotherapy; Ipilimumab